Enhancing Teacher Quality in Indonesia: A Systematic Literature Review of the PPG Prajabatan Program Perspectives - Kurniadi, Tedy (Langue (Journal of Language and Education), 2025)
This systematic literature review (SLR) explores the Pendidikan Profesi Guru (PPG) Prajabatan in Indonesia, a crucial initiative aimed at enhancing teacher quality and effectiveness. Established under the Ministry of Education Regulation No. 87 of 2013, the PPG program serves as a mandatory professional education pathway for aspiring teachers, focusing on improving their pedagogical knowledge and teaching skills. The review synthesizes perspectives from various stakeholders regarding the program's effectiveness, challenges, and areas for improvement, particularly analyzing studies published between 2018 and 2024.The findings reveal that while the PPG program significantly enhances teaching skills and confidence among participants, challenges persist, particularly concerning training facilities and support systems. Many alumni expressed dissatisfaction with logistical aspects of the program, indicating a need for improvements. Additionally, while interactive teaching methods proved beneficial, limitations in language proficiency development were noted. The review concludes that addressing these challenges is essential for maximizing the program's impact on educational quality in Indonesia. Future iterations should focus on enhancing facilities, fostering greater engagement among participants and coordinators, and integrating more language-focused activities to improve communication skills within a multilingual context.